Pathogenesis of Age-Related Cataract: A Systematic Review of Proteomic Studies - Karakosta, Christina; Tzamalis, Argyrios; Aivaliotis, Michalis; Tsinopoulos, Ioannis (Current Proteomics, 2021)
Aim: The aim of this systematic review is to identify all the available data on human lens proteomics with a critical role in age-related cataract formation in order to elucidate the physiopathology of the aging lens. Methods: We searched on Medline and Cochrane databases. The search generated 328 manuscripts. We included nine original proteomic studies that investigated human cataractous lenses. Results: Deamidation was the major age-related post-translational modification. There was a significant increase in the amount of αA-crystallin D-isoAsp58 present at all ages, while an increase in the extent of Trp oxidation was apparent in cataract lenses when compared to aged normal lense. During aging, enzymes with oxidized cysteine at critical sites included GAPDH, glutathione synthase, aldehyde dehydrogenase, sorbitol dehydrogenase, and PARK7. Conclusion: D-isoAsp in αA crystallin could be associated with the development of age-related cataract in humans by contributing to the denaturation of a crystallin and decreasing its ability to act as a chaperone. Oxidation of Trp may be associated with nuclear cataract formation in humans, while the role of oxidant stress in age-related cataract formation is dominant.
Keywords: lens